Toxic metals in the crude propolis and its transfer rate to the ethanolic extract - Orsi, R. O. [UNESP]; Barros, D. C.B. [UNESP]; Silva, R. C.M. [UNESP]; Queiroz, J. V. [UNESP]; Araújo, W. L.P. [UNESP]; Shinohara, A. J. [UNESP] (Universidade Estadual de Feira de Santana, 2018)
Concentrations of six toxic metals (Ni, Cr, Hg, Cd, Pb and Sn) in 106 samples of Brazilian crude propolis and the transfer rate of these contaminants to ethanolic extract of propolis were evaluated by atomic absorption spectrophotometry. The results show the presence of all the analyzed metals in the samples of crude propolis of São Paulo and Minas Gerais States. Regarding the transfer of these metals to ethanolic extract of propolis, a significant reduction was observed for all metals analyzed. The crude propolis can be considered as an indicator of toxic metals in the environment and the reduction observed in the ethanolic extract of propolis makes the product safe for consumption.
Keywords: Beekeeping; Environment; Food safety; Toxicity.